Gravity Falls. Lost legends - Hirsch, Alex, 1985- (Glendale, California : Disney Press, 2018)
A graphic novel collection features four strange stories from the sleepy town of Gravity Falls. The first story, Face It, is about Pacifica summoning a monster who steals Mabel's face. The second story, Comix Up, is about Stan getting trapped in a world of comics. In Don't Dimension It, Mabel gets pulled into a multi-verse filled with many different Mabels. And in Pines Brothers: The Jersey Devil's in the Details, a young Stan and Ford attempt to catch a supernatural jewel thief.
Face it -- Comix up! -- Don't dimension it -- The Jersey devil's in the details.
At head of title: Disney.
3-6
GN410L
3.7
Keywords: Twins -- Comic books, strips, etc -- Fiction; Twins -- Juvenile fiction; Supernatural -- Fiction; Paranormal fiction; Paranormal fiction; Comics (Graphic works); Graphic novels; Science fiction comics; Fantasy comics; Graphic novels; Graphic novel adaptations